INTERNET ACCESS IN KENYAN UNIVERSITY LIBRARIES SINCE 1990S - JN Odero, Damaris; M. Mutula, Stephen (Malaysian Journal of Library and Information Science, 2017)
Presents literature based historical review of Internet access in Kenyan university libraries since the first connectivity in the country in 1994. The literature is based on four major newspapers in Kenya that are reputed for tracking Internet growth and its integration in the country’s institutions. These major newspapers are The Standard, Daily Nation, Kenya Times and East African. Despite the fact that the Internet is increasingly being adopted in most universities the world over, universities in Kenya are struggling to provide efficient internet access to students and staff because of several constraints such as costs, infrastructure, policy and poor management vision. The findings of this work identify several areas that need attention to enhance a wider adoption and use of the Internet by university libraries in Kenya. Moreover, there is a need for demonstrated interventions that will provide conditions that enhance individual employees’ interaction, acceptability and use of the Internet. In addition, university libraries should equip their employees with the required levels of Internetrelated knowledge and skills. From a practical perspective, the training offered to the staff should be designed to not only offer mastery of the skills, but also promote positive perceptions and appreciations of the technology. There is also need for libraries to identify appropriate proactive measures that can promote positive Internet response. Similarly, university libraries require clear drawn-up ICT policies specifying the envisioned role of both general and specific ICTs. Extending the service to library clients at a subsidized fee should supplement the recurrent expenditure incurred in the provision of the service